THE USE OF ARTIFICIAL INTELLIGENCE IN NEWS PRODUCTION PROCESSES - Wahidar, Tutut Ismi; Muradi, Baiqra (Jurnal Ilmu Komunikasi, 2025)
The development of artificial intelligence (AI) technology shows a significant transformation in various fields, including journalistic practices in the era of the Fourth Industrial Revolution. The wave of AI development, which includes Internet AI, data-based AI, generative AI, and Autonomous AI, has increased the efficiency and effectiveness of news production and distribution processes. However, the application of AI in the world of journalism poses various ethical challenges, such as algorithmic bias, system opacity, the risk of misinformation dissemination, and a decrease in human accountability. This research examines the implications of AI use in journalistic practices from an ethical perspective, highlighting the need for critical human oversight to maintain the integrity, accuracy, and balance of news. The results of this study indicate that although AI has the potential to enhance the quality and efficiency of journalism, its application must be accompanied by the development of technological competencies for journalists and continuous oversight to ensure that journalistic ethical principles are maintained in the news automation process